Rawḍa-yi taslīm (taṣavvurāt) - Ṭūsī, Naṣīr al-Dīn (Miras Maktoob, ISBN: 9789004365452., 2019)
Naṣīr al-Dīn Ṭūsī (d. 672/1274) was an influential philosopher, theologian, mathematician and astronomer, besides being the first director of the famous observatory at Marāghah near Tabriz as well as a man of politics. Author of a large number of scholarly works, he is especially famous for such treatises as his Tajrīd al-iʿtiqād on theology, the Zīj-i Īlkhānī on astronomy, the Ḥall mushkilāt al-Ishārāt , his influential commentary on Avicenna's (428/1037) Kitāb al-ishārāt wal-tanbīhāt on philosophy and logic, and his Akhlāq-i Nāṣirī on ethics. Ṭūsī spent at least half of his academic and political life among the Nizārī branch of the Ismailis, first in Quhistan in eastern Iran, and then in Alamut in the north and other Ismaili strongholds. The Persian work published here originated as a lecture series on Nizārī Ismaili doctrine, given by Ṭūsī in Alamut. The edition is a much improved version of the one by Ivanov, based on better manuscripts, unavailable to him.